A Quasi-Domesticate Relic Hybrid Population of Saccharomyces cerevisiae × S. paradoxus Adapted to Olive Brine - Pontes, Ana; Čadež, Neža; Gonçalves, Paula; Sampaio, José Paulo (Frontiers in Genetics, 2019)
The adaptation of the yeast Saccharomyces cerevisiae to man-made environments for the fermentation of foodstuffs and beverages illustrates the scientific, social and economic relevance of microbe domestication. Here we address a yet unexplored aspect of S. cerevisiae domestication, that of the emergence of lineages harboring some domestication signatures but that do not fit completely in the archetype of a domesticated yeast, by studying S. cerevisiae strains associated with processed olives, namely table olives, olive brine, olive oil and alpechin. We confirmed earlier observations that reported that the Olives population results from a hybridization between S. cerevisiae and S. paradoxus. We concluded that the olive hybrids form a monophyletic lineage and that the S. cerevisiae progenitor belonged to the wine population of this species. We propose that homoploid hybridization gave rise to a diploid hybrid genome, which subsequently underwent the loss of most of the S. paradoxus sub-genome. Such a massive loss of heterozygosity was probably driven by adaptation to the new niche. We observed that olive strains are more fit to grow and survive in olive brine than control S. cerevisiae wine strains and that they appear to be adapted to cope with the presence of NaCl in olive brine through expansion of copy number of ENA genes. We also investigated whether the S. paradoxus HXT alleles retained by the Olives population were likely to contribute to the observed superior ability of these strains to consume sugars in brine. Our experiments indicate that sugar consumption profiles in the presence of NaCl are different between members of the Olives and Wine populations and only when cells are cultivated in nutritional conditions that support adaptation of their proteome to the high salt environment, which suggests that the observed differences are due to a better overall fitness of olives strains in the presence of high NaCl concentrations. Although relic olive hybrids exhibit several characteristics of a domesticated lineage, tangible benefits to humans cannot be associated with their phenotypes. These strains can be seen as a case of adaptation without positive or negative consequences to humans, that we define as a quasi-domestication.